2002
DOI: 10.1128/iai.70.8.4399-4405.2002
|View full text |Cite
|
Sign up to set email alerts
|

Flavohemoglobin Hmp ProtectsSalmonella entericaSerovar Typhimurium from Nitric Oxide-Related Killing by Human Macrophages

Abstract: Survival of macrophage microbicidal activity is a prerequisite for invasive disease caused by the enteric pathogen Salmonella enterica serovar Typhimurium. Flavohemoglobins, such as those of Escherichia coli, Salmonella, and yeast, play vital roles in protection of these microorganisms in vitro from nitric oxide (NO) and nitrosative stress. A Salmonella hmp mutant defective in flavohemoglobin (Hmp) synthesis exhibits growth that is hypersensitive to nitrosating agents. We found that respiration of this mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
119
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 44 publications
3
119
0
Order By: Relevance
“…By demonstrating an unequivocal contribution of Hmp to Salmonella virulence, we have been able to expand significantly upon an earlier report that Hmp modestly enhances Salmonella survival in cultured macrophages (50). Moreover, our finding that Hmp is required for persistent infection of Salmonella in mice suggests that host-derived RNS are important during microbial persistence as well as acute infection.…”
Section: Discussionsupporting
confidence: 58%
“…By demonstrating an unequivocal contribution of Hmp to Salmonella virulence, we have been able to expand significantly upon an earlier report that Hmp modestly enhances Salmonella survival in cultured macrophages (50). Moreover, our finding that Hmp is required for persistent infection of Salmonella in mice suggests that host-derived RNS are important during microbial persistence as well as acute infection.…”
Section: Discussionsupporting
confidence: 58%
“…Considering that macrophages produce a large amount of NO to control infection (18)(19)(20) our seemingly paradoxical results can be rationalized if NO production by bacteria and macrophages is separated in time, leading to opposite outcomes. Indeed, it is well established that superoxide generation begins immediately after phagocytosis of bacteria.…”
Section: No From B Anthracis Is An Essential Virulence Factormentioning
confidence: 99%
“…Specifically, both S. typhimurium and Escherichia coli produce NO (10,11), although the physiological significance of this is unclear. In E. coli, it has been reported that periplasmic nitrite reductase (NrfA; pentaheme periplasmic cytochrome c nitrite reductase) has a dual role in NO homeostasis; not only is it responsible for production of NO (11) but is also capable of detoxification of NO to NH 4 ϩ or N 2 O anaerobically (12,13). However, the major role of NrfA in E. coli is as a catalyst of the 6-electron reduction of NO 2 Ϫ to NH 4 ϩ (14).…”
mentioning
confidence: 99%
“…Enterobacteria possess several NO-detoxifying mechanisms, the most prominent being the flavohemoglobin Hmp (3)(4)(5)(6) and the flavorubredoxin NorV (7). These enzymes detoxify incoming NO both aerobically (Hmp) and anoxically (NorV), converting the toxic gas to NO 3 Ϫ or N 2 O, respectively (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation